THE INFLUENCE OF GENDER AND FAMILY IN ONLINE PARTICIPATION OF TEENAGERS AT SOCIAL RISK - Gerulaitienė, Eglė; Šidagytė, Jolita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Internet is a mean of mass information and fulfills the traditional functions of a public space without doubts. Participation in the virtual space is defined as a problematic use of the Internet process which damages the disadvantaged young person's personality, which is already characterized by a lack of social skills, communication, feelings of expression issues. The majority of young people are attracted by internet space, by its anonymity and availability. The aim of the research is to analyze the influence of gender and family aspects in online participation of teenagers at social risk. The research showed that the internet provides the great and additional opportunities to teenagers at social risk, something they don’t get in their families. Children living with grandparents or with only one parent are more active users of Internet social networks in comparison with other children. They seldom recognize the Internet dangers and more quickly become emotionally dependent on the Internet. The adults’ control or its absence determines the expression and frequency of online participation of teenagers at social risk. The girls more frequently recognize the dangers of virtual space than the boys do; but the girls use to publish more information about themselves. The research results show that the participation of teenagers at social risk in social networks is unconscious. Young people are not able to “filter” and select proper information, usually equate the virtual world with reality. Online participation of teenagers is reasoned by satisfaction of needs, parents’ inattention and search for new acquaintances.